MENA Regional Synthesis on the Teacher Policies Survey : Key Findings from Phase 1 - World Bank (Washington, DC, 2015)
This report summarizes the main findings of the first phase of the regional study on teacher policies which draws heavily from the SABER-Teachers methodological papers and country reports. It presents the methodology of the SABER-Teachers benchmarking exercise; provides a preliminary analysis of the regional trends in teacher policies based on data collection and analytical tools developed by HDNED as well as the country reports produced by the SABER-Teachers team; and discusses the next steps for the regional work on teacher policies.